Neural correlates of the numerical distance effect in children - Mussolin, Christophe; Noel, Marie-Pascale; Pesenti, Mauro; Grandin, Cécile; De Volder, Anne (Frontiers in Psychology, 2013)
In number comparison tasks, the performance is better when the distance between the two numbers to compare increases. During development this so-called numerical distance effect decreases with age and the neuroanatomical correlates of these age-related changes are poorly known. Using functional magnetic resonance imaging, we recorded the brain activity changes in children aged from 8 to 14 years while they performed a number comparison task on pairs of Arabic digits and a control colour comparison task on non-numerical symbols. On the one hand, we observed developmental changes in the recruitment of frontal regions and the left intraparietal sulcus, with lower activation as the age increased. On the other hand, we found that a behavioural index of selective sensitivity to the numerical distance effect was positively correlated with higher brain activity in a right lateralized occipito-temporo-parietal network including the intraparietal sulcus. This leads us to propose that the left intraparietal sulcus would be engaged in the refinement of cognitive processes involved in number comparison during development, while the right intraparietal sulcus would underlie the semantic representation of numbers and its activation would be mainly affected by the numerical proximity between them.